Pemberdayaan Karang Taruna melalui Pemanfaatan Limbah Sekam Padi menjadi Briket sebagai Energi Alternatif di Desa Sungai Tuan Ulu - Eddy Elminsyah Jaya (LPPM Universitas Muhadi Setiabudi, 2026)
This community service activity aims to enhance community capacity in utilizing rice husk waste into value-added products in the form of briquettes as an alternative fuel. The activity was conducted in Sungai Tuan Ulu Village, Astambul District, Banjar Regency, targeting members of the “Kasta” Youth Organization and local communities. The implementation method employed a participatory approach through three main stages: socialization, technical training, and mentoring. The results indicate an improvement in community knowledge and skills in processing rice husk into briquettes. Participants were able to independently practice the production process using a simple briquette molding tool, although some technical constraints were found in product consistency. Furthermore, this activity contributes to reducing agricultural waste and creating new economic opportunities based on local resources. This study demonstrates that the integration of community empowerment and appropriate technology is effective in promoting sustainable waste management and improving local economic conditions.